Research Progress on Extracellular Matrix Involved in the Development of Preeclampsia - Wang, Xin; Zhang, Qi; Ren, Yi; Liu, Chao; Gao, Huijie (Current Protein and Peptide Science, 2024)
Preeclampsia (PE) is a serious pregnancy complication, and its primary clinical manifestations are gestational hypertension and proteinuria. Trophoblasts are responsible for the basic functions of the placenta during placental development; recent studies have revealed that placental “shallow implantation” caused by the decreased invasiveness of placental trophoblasts plays a crucial role in PE pathogenesis. The interaction between the cells and the extracellular matrix (ECM) plays a crucial role in trophoblast proliferation, differentiation, and invasion. Abnormal ECM function can result in insufficient migration and invasion of placental trophoblasts, thus participating in PE. This article summarizes the recent studies on the involvement of ECM components, including small leucine-rich proteoglycans, syndecans, glypicans, laminins, fibronectin, collagen, and hyaluronic acid, in the development of PE. ECM plays various roles in PE development, most notably by controlling the activities of trophoblasts. The ECM is structurally stable and can serve as a biological diagnostic marker and therapeutic target for PE.
Keywords: matrix metalloproteinases